2020
DOI: 10.2196/preprints.20786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient Satisfaction With Telemedicine During the COVID-19 Pandemic: Retrospective Cohort Study (Preprint)

Abstract: BACKGROUND New York City was the international epicenter of the COVID-19 pandemic. Healthcare providers responded by rapidly transitioning from in-person to video visits. Telemedicine (i.e. video visits) is a potentially disruptive innovation; however, little is known about patient satisfaction with this emerging alternative to the traditional clinical encounter. OBJECTIVE To determine if patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
2
0
2
Order By: Relevance
“…Centers for Medicare and Medicaid Services made telemedicine accessible during the pandemic by paying physicians the same rate for telemedicine services as in-person visits for all diagnoses [ 25 ]. Thus, telemedicine has been widely implemented and is now being studied across various subspecialties through evaluation of patient satisfaction and utilization rates [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centers for Medicare and Medicaid Services made telemedicine accessible during the pandemic by paying physicians the same rate for telemedicine services as in-person visits for all diagnoses [ 25 ]. Thus, telemedicine has been widely implemented and is now being studied across various subspecialties through evaluation of patient satisfaction and utilization rates [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by empiric medication prescribing based on symptomology. In smaller studies, telemedicine video visits have been shown to have no difference in clinical outcomes while allowing for lower costs and higher patient satisfaction, in comparison to in-person consultations [ 26 ]. It is unclear whether greater patient satisfaction in prior studies could be tied to increased medication prescribing or satisfaction with telemedicine itself, and further studies on patient satisfaction with telemedicine are warranted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…El investigador concluyó que, a mayor calidad de atención mejora satisfacción de los pacientes. (17) Nuestros hallazgos demostraron que al cruzar la variable fiabilidad evidencia una correlación moderada entre las variables satisfacción y fiabilidad con un valor de Rho Spearman=,546, donde el nivel de significatividad es 0,000 menor a 0,05, lo que quiere decir que, a mayor fiabilidad, mejora la satisfacción de los pacientes mediante la telemedicina (TICs). Sin embargo, no se encontró resultados similares en otros estudios.…”
Section: Discussionunclassified
“…Obtuvieron como resultados que las puntuaciones de las visitas por video fueron de 94,4% y la satisfacción fue de 94,9%. Concluyeron que la satisfacción del paciente con las visitas por video fue favorable en comparación con las visitas en persona, respaldando el uso de la visita por video como una alternativa viable a las visitas tradicionales en persona (17). En el 2020, García y Col, realizaron una investigación prospectivo observacional con el objetivo de evaluar la satisfacción del paciente y del proveedor sobre el uso de telemedicina en Otorrinolaringología.…”
unclassified